Site-specific replacement of the thymine methyl group by fluorine in thrombin binding aptamer significantly improves structural stability and anticoagulant activity. Issue 22 (17th November 2015) - Virgilio, Antonella; Petraccone, Luigi; Vellecco, Valentina; Bucci, Mariarosaria; Varra, Michela; Irace, Carlo; Santamaria, Rita; Pepe, Antonietta; Mayol, Luciano; Esposito, Veronica; Galeone, Aldo
Abstract: Here we report investigations, based on circular dichroism, nuclear magnetic resonance spectroscopy, molecular modelling, differential scanning calorimetry and prothrombin time assay, on analogues of the thrombin binding aptamer (TBA) in which individual thymidines were replaced by 5-fluoro-2′-deoxyuridine residues. The whole of the data clearly indicate that all derivatives are able to fold in a G-quadruplex structure very similar to the 'chair-like' conformation typical of the TBA. However, only ODNs TBA-F4 and TBA-F13 have shown a remarkable improvement both in the melting temperature (ΔTm ≈ +10) and in the anticoagulant activity in comparison with the original TBA. These findings are unusual, particularly considering previously reported studies in which modifications of T4 and T13 residues in TBA sequence have clearly proven to be always detrimental for the structural stability and biological activity of the aptamer. Our results strongly suggest the possibility to enhance TBA properties through tiny straightforward modifications.